Search transition as a measure of effort in information retrieval interaction. Issue 1 (2013) - Nordlie, Ragnar; Pharo, Nils
Abstract: In this article we introduce the concept of search transitions as a unit for measuring the effort invested by searchers in information retrieval interaction. The concept is discussed and compared to traditional measures of effort, such as time. To investigate the usability of the search transition measure we have performed an analysis of 149 logs in an IR system indexing a collection of 650.000 Wikipedia articles. Our findings show that search transitions correlate with other, more mechanistic, effort measures. Additional experiments are necessary to investigate if it is a better measure of effort than e.g. number of documents examined.